Bioconversion of Low Quality Lignocellulosic Agricultural waste into Edible Protein by Pleurotus djamor (Rumph) Boedijn - Chauhan, Praneet; Gupta, Dharmesh (International Journal of Bio-resource and Stress Management, 2023)
` The experiments were carried out at the Mushroom Research Laboratory, Department of Plant Pathology, Dr. YS Parmar University of Horticulture and Forestry, Nauni, Solan (H.P.), India during 2010-2012. The culture of Pleurotus djamor was procured from Directorate of Mushroom Research, Solan and was maintained on PDA medium. Eight different substrates viz., wheat straw, corn cobs, lantana twigs, rice straw, poplar leaves, parthenium leaves, sugarcane bagasse, saw dust alone or wheat straw in combination with saw dust, wheat bran, cotton seed meal, urea, CAN, waste paper, lantana twigs and corn cobs were evaluated for the yield performance and biological efficiency (BE) of P. djamor. Among the various substrates Lantana twigs was found highly suitable with 75.23% BE for the cultivation of Pink oyster mushroom (Pleurotus djamor). Combination of wheat straw+wheat bran (9:1) and wheat straw+cotton seed meal (9:1) gave better yield with biological efficiency of 78.60% and 78.56%, respectively `````````````````````````````````````````````````````````````````````````